2008
DOI: 10.1101/gad.1687308
|View full text |Cite
|
Sign up to set email alerts
|

Sfrp5 coordinates foregut specification and morphogenesis by antagonizing both canonical and noncanonical Wnt11 signaling

Abstract: Cell identity and tissue morphogenesis are tightly orchestrated during organogenesis, but the mechanisms regulating this are poorly understood. We show that interactions between Wnt11 and the secreted Wnt antagonist secreted frizzled-related protein 5 (Sfrp5) coordinate cell fate and morphogenesis during Xenopus foregut development. sfrp5 is expressed in the surface cells of the foregut epithelium, whereas wnt11 is expressed in the underlying deep endoderm. Depletion of Sfrp5 results in reduced foregut gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
166
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(181 citation statements)
references
References 76 publications
14
166
1
Order By: Relevance
“…In Xenopus embryos, Wnt/b-catenin activity must be suppressed in anterior endoderm to maintain foregut identity and to allow liver and pancreas development, whereas high Wnt/b-catenin activity in the posterior endoderm promotes intestinal fate (McLin et al, 2007). Later it was shown that SFRP5-mediated suppression of both canonical and non-canonical Wnt activities (via inhibition of Wnt11) in the anterior endoderm is required for foregut specification and morphogenesis, while non-canonical Wnt activities in the posterior endoderm promote hindgut morphogenesis in Xenopus (Li et al, 2008). Determining the degree of parallelism in this process in the mammalian embryo will be important; it also has to be stated that much more precision on the timing and levels of signaling will be needed with respect to how specific organ territories are defined.…”
Section: Figmentioning
confidence: 99%
“…In Xenopus embryos, Wnt/b-catenin activity must be suppressed in anterior endoderm to maintain foregut identity and to allow liver and pancreas development, whereas high Wnt/b-catenin activity in the posterior endoderm promotes intestinal fate (McLin et al, 2007). Later it was shown that SFRP5-mediated suppression of both canonical and non-canonical Wnt activities (via inhibition of Wnt11) in the anterior endoderm is required for foregut specification and morphogenesis, while non-canonical Wnt activities in the posterior endoderm promote hindgut morphogenesis in Xenopus (Li et al, 2008). Determining the degree of parallelism in this process in the mammalian embryo will be important; it also has to be stated that much more precision on the timing and levels of signaling will be needed with respect to how specific organ territories are defined.…”
Section: Figmentioning
confidence: 99%
“…Unlike Dkks, which specifically inhibit Wnt/b-catenin signaling, sFRPs can also inhibit noncanonical Wnt/PCP ( planar cell polarity) signaling (Li et al 2008b;Satoh et al 2008;Matsuyama et al 2009;Sugiyama et al 2010), which is not surprising, as they bind to both types of Wnts. Inhibition of PCP signaling, which antagonizes Wnt/b-catenin signaling (Yan et al 2001;Schwarz-Romond et al 2002;Simons et al 2005;Li et al 2011), may also explain why sFRPs can activate Wnt/b-catenin signaling (Swain et al 2005).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Both are expressed in mesenchyme in complementary antitooth patterns. sfrp5 has been described as a Wnt inhibitor in several systems (27,28), an integrator of Wnt-BMP signaling in the zebrafish gut (29), and a regulator of mouse incisor renewal (30). bmper has been reported as both a positive and negative mediator of BMP signaling in other organs of the mouse, frog, and fly (31)(32)(33), and as an antagonist of BMP in mouse incisor ameloblasts (34).…”
Section: Cichlid Tooth and Taste Bud Fields Are Specified From A Commonmentioning
confidence: 99%